Energy efficient with time synchronised and service coverage guarantee in wireless sensor networks. (2018) - Gherbi, Chirihane; Aliouat, Zibouda; Benmohammed, Mohamed
In this paper, a novel hierarchical approach called distributed energy efficient adaptive clustering protocol with data gathering, load-balancing and self-adaptation (ACP) is proposed for wireless sensor network. We have proposed (ACP) approach to reach the following objectives: reduce the overall network energy consumption, balance the energy consumption among the sensors and extend the lifetime of the network, the clustering must be completely distributed, the clustering should be efficient in complexity of message and time, the cluster-heads should be well-distributed across the network, the load balancing should be done well, the clustered WSN should be fully-connected. We consider the problem of conserving energy by turning off the node's radio for periods of a fixed time length. As a result transmission power of the node is reduced, which subsequently reduce the energy consumption of the node. Our proposed work is simulated through network simulator (NS-2). Simulations show that (ACP) clusters have good performance characteristics.